Source apportionment of the sediments entering dam using lithological and mineralogical studies - S. Afshar; B. Saghafian; H.R. Vosoughifar (Global Journal of Environmental Science and Management)
The present study was carried out to determine the possible origins of sediments entering Taleghan Dam in northern part of Iran, in order to avoid further sedimentation and helping in extension of the useful life of the proposed dam. This was performed by XRD analysis. To do so, first of all, sediment sampling points were positioned along the Taleghan River. The collected samples, after coding, were transferred to the laboratory for mineralogical testing. Then, the samples were exposed to X-ray diffraction analysis. The experimental results were compared with data from geology, land cover land use and slope maps in order to find the possible primary origins of deposits in the Taleghan Dam. Furthermore, the geological formations and physiographical parameter such as slope were also analyzed to test erodibility of the formations. The results showed that most sediment samples in Taleghan are of sedimentary sandstone, mainly containing the quartz and plagioclase minerals (quartz sandstone and arkose sandstone). The findings also showed that calcite and dolomite were abundant in the collected samples, while aragonite and anthracite were found to a lesser extent in the samples. Accordingly, acidic and alkaline formations, mudstone, and siltstone of Karaj area formations, the gypsum of upper red formation, particularly at places with steep slope with a dominance of rangeland land use type, are main origins of sediments in the Taleghan reservoir. In another hand, the control of sediments at these areas would substantially decrease total sediment yields of the entire basin as in the dam reservoir.